2012
DOI: 10.1002/jso.23272
|View full text |Cite
|
Sign up to set email alerts
|

Expression of survivin and livin predicts early recurrence in non‐muscle invasive bladder cancer

Abstract: Expression of survivin and livin may influence the prognosis of NIMBC. This finding opens new perspectives for Survivin and livin prediction of early recurrence in NIMBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
(32 reference statements)
3
17
0
Order By: Relevance
“…It has been demonstrated to be expressed in transformed cells and multiple types of malignant tumor, including neuroblastoma (20) as well as carcinomas of the bladder (21,22), lung (23), nasopharynx (24), kidney (25), liver (26), colon/rectum (27), skin (28), bone (29) and stomach (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated to be expressed in transformed cells and multiple types of malignant tumor, including neuroblastoma (20) as well as carcinomas of the bladder (21,22), lung (23), nasopharynx (24), kidney (25), liver (26), colon/rectum (27), skin (28), bone (29) and stomach (30).…”
Section: Discussionmentioning
confidence: 99%
“…Livin, a novel member of the inhibitor of apoptosis (IAP) protein family, is not detected in the majority of normal tissues, however, is highly expressed in various types of human malignancy (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Increased activity of this protein may be used as a reliable prognostic factor for initial and late resistance to chemotherapeutic drugs in certain types of human tumor (31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…High nuclear livin protein expression is found to predict satisfactory prognosis of renal cell carcinoma [19], and children with acute lymphoblastic leukemia positive for livin protein are reported to have a satisfactory prognosis [20]. However, it appears that high expression of the livin gene predicts poor prognosis of breast cancer [21], and high livin protein expression is reported to be associated with early-stage relapse of breast cancer and the lymph node metastasis of ampullary carcinoma [22, 23]. In addition, livin expression is found not to be associated with the prognosis of HCC [24], and the expression of the livin gene is reported not to be related to the survival period of patients with non-small-cell lung cancer [6].…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that survivin/BIRC5 has a higher expression in adrenocortical tumors than in normal adrenal glands and that its expression correlates with prognosis in ACC group [36]. Several studies indicated that livin and survivin play together an important role in the tumorigenesis and in the clinical outcome of several human cancers [18, 37]. The expression of other components of IAP family has been poorly evaluated in adrenocortical tissues [22].…”
Section: Introductionmentioning
confidence: 99%